Semantics preserving MapReduce process for RDB to RDF transformation. (2015) - Lim, Kyung-Bin; Jun, Hee-Gook; Kim, Hyoung-Joo
RDB2RDF approaches have been proposed and standardised by W3C, which publishes relational data to semantic web by converting relational data into RDF formatted data. We propose a system that automatically transforms relational data into RDF data and creates OWL ontology based on the schema of database. Some approaches have been proposed, but most of them did not fully make use of schema information to extract rich semantics, nor did they experiment on large databases for performance. We utilise Hadoop framework in transformation process, which enables distributed system for scalability. We present mapping rules that implement augmented direct mapping to create local ontology with rich semantics. The results show that our system successfully transforms relational data into RDF data with OWL ontology, with satisfactory performance on large-sized databases.